Risk Factors for Acute Kidney Injury in Adult Patients With COVID-19: A Systematic Review and Meta-Analysis - Cai, Xiaoyue; Wu, Guiming; Zhang, Jie; Yang, Lichuan (Frontiers in Medicine, 2021)
Background and Objective Since December 2019, coronavirus disease 2019 (COVID-19) has spread rapidly around the world. Studies found that the incidence of acute kidney injury (AKI) in COVID-19 patients was more than double the incidence of AKI in non-COVID-19 patients[1,2]. Some findings confirmed that AKI is a strong independent risk factor for mortality in patients with COVID-19 and is associated with a 3-fold increase in the odds of in-hospital mortality[14]. However, little information is available about AKI in COVID-19 patients. This study aimed to analyse the risk factors for AKI in adult patients with COVID-19. Methods A systematic literature search was conducted in PubMed, EMBASE, Web of Science, the Cochrane Library, CNKI, VIP and WanFang Data from 1 December 2019 to 30 January 2021. We extracted data from eligible studies to compare the effects of age, sex, chronic diseases and potential risk factors for AKI on the prognosis of adult patients with COVID-19. Results In total, 38 studies with 42,779 patients were included in this analysis. The meta-analysis showed that male sex (OR =1.37), older age (MD=5.63), smoking (OR =1.23), obesity (OR = 1.12), hypertension (OR=1.85), diabetes (OR=1.71), pneumopathy (OR=1.36), cardiovascular disease (OR =1.98), cancer (OR = 1.26), chronic kidney disease (CKD) (OR=4.56), mechanical ventilation (OR= 8.61) and the use of vasopressors (OR=8.33) were significant risk factors for AKI (P＜0.05). Conclusions AKI is a common and serious complication of COVID-19. Overall, male sex, age, smoking, obesity, hypertension, diabetes, pneumopathy, cardiovascular disease, cancer, CKD, mechanical ventilation and the use of vasopressors were independent risk factors for AKI in adult patients with COVID-19. Clinicians need to be aware of these risk factors to reduce the incidence of AKI.